Prospect theory and hedging risks - Udo Broll; Martín Egozcue; Wing-Keung Wong; Ričardas Zitikis (Technische Universität Dresden, Fakultät Wirtschaftswissenschaften, 2010)
The prospect theory is one of the most popular decision-making theories. It is based on the S-shaped utility function, unlike the von Neumann and Morgenstern (NM) theory, which is based on the concave utility function. The S-shape brings in mathematical challenges: simple extensions and generalizations of NM theory into the prospect theory cannot be frequently achieved. For example, the nature of monotonicity of the indifference curve depends on the underlying mean. Price hedging decisions also become more complex within the prospect theory. We discuss these topics in detail and offer a general result concerning the sign of a covariance from which we then infer desired properties of the indifference curve and also justify hedging decisions within the prospect theory. We illustrate our general considerations with a thoroughly worked out example.
Keywords: D01; D03; D21; D81; 330; prospect theory; mean-variance model; indifference curve; price uncertainty; hedging; Theorie der Unternehmung; Produktion; Entscheidung bei Unsicherheit; Hedging; Prospect Theory; Preis; Risiko; Theorie